Retinal Toxicity Induced by a Novel β-secretase Inhibitor in the Sprague-Dawley Rat. (June 2015) - Fielden, Mark R.; Werner, Jonathan; Jamison, Jeff A.; Coppi, Aldo; Hickman, Dean; Dunn, Robert T.; Trueblood, Esther; Zhou, Lei; Afshari, Cynthia A.; Lightfoot-Dunn, Ruth
Β-Secretase 1 (BACE1) represents an attractive target for the treatment of Alzheimer's disease. In the course of development of a novel small molecule BACE1 inhibitor (AMG-8718), retinal thinning was observed in a 1-month toxicity study in the rat. To further understand the lesion, an investigational study was conducted whereby rats were treated daily with AMG-8718 for 1 month followed by a 2-month treatment-free phase. The earliest detectable change in the retina was an increase in autofluorescent granules in the retinal pigment epithelium (RPE) on day 5; however, there were no treatment-related light microscopic changes observed in the neuroretina and no changes observed by fundus autofluorescence or routine ophthalmoscopic examination after 28 days of dosing. Following 2 months of recovery, there was significant retinal thinning attributed to loss of photoreceptor nuclei from the outer nuclear layer. Electroretinographic changes were observed as early as day 14, before any microscopic evidence of photoreceptor loss. BACE1 knockout rats were generated and found to have normal retinal morphology indicating that the retinal toxicity induced by AMG-8718 was likely off-target. These results suggest that AMG-8718 impairs phagolysosomal function in the rat RPE, which leads to photoreceptor dysfunction and ultimately loss of photoreceptors.